2022
DOI: 10.1177/23971983221102688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of skin phototype on quantitative nailfold capillaroscopy

Abstract: Objectives: To determine the impact of Fitzpatrick scale-based skin phototype on visualization of capillary density using nailfold capillaroscopy in healthy Indian adults. Methods: In this cross-sectional study, healthy adults were examined for nailfold capillaroscopy findings utilizing a portable capillary microscope at 800× magnification. Photographs of two contiguous areas measuring 1 mm2 each of the distal row of capillaries were captured. Images were captured from the central area of all fingers except th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…To evaluate this, nailfold capillaroscopy examinations in healthy adults are first needed. Recently, a study in healthy adults was performed in India by Bairwa et al ( 27 ) In line with our results, they found that the density of capillaries visualized by nailfold capillaroscopy decreases as the skin pigmentation increases. Of note, they included 118 healthy adults with Type III, IV, V, and VI skin phototypes (classified by Standard Fitzpatrick classification of skin phototype).…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate this, nailfold capillaroscopy examinations in healthy adults are first needed. Recently, a study in healthy adults was performed in India by Bairwa et al ( 27 ) In line with our results, they found that the density of capillaries visualized by nailfold capillaroscopy decreases as the skin pigmentation increases. Of note, they included 118 healthy adults with Type III, IV, V, and VI skin phototypes (classified by Standard Fitzpatrick classification of skin phototype).…”
Section: Discussionsupporting
confidence: 90%